Transcription-dependent and transcription-independent functions of the classical progesterone receptor in Xenopus ovaries - Liu, Xun (University of Ottawa (Canada), 2004)
The physiological functions of the classical progesterone receptor (XPR) in regulating oocyte maturation and ovulation in Xenopus laevis remain controversial. Using antibodies generated against cloned XPR, I demonstrated here that the somatic follicle cells expressed an 80 kDa XPR protein, termed XPR-1. XPR-1 underwent progesterone-induced, proteasome-mediated degradation. A smaller (∼70 kDa) XPR protein, termed XPRo, was expressed in oocytes, but not in follicle cells. XPRo underwent progesterone-induced hyperphosphorylation, but not degradation. Treating isolated ovaries with progesterone caused oocyte maturation and the release of the mature oocytes from the ovaries (ovulation). Actinomycine D, a general transcription inhibitor, did not interfere with progesterone-induced oocyte maturation but blocked ovulation so that mature oocytes were trapped in the follicles. These results demonstrated that progesterone had dual functions in the process of ovulation: transcription-dependent follicle rupture and transcription-independent oocyte maturation. Furthermore, our results suggest that the dual functions of progesterone in Xenopus ovaries are mediated by the two forms of XPR proteins differentially expressed in the follicle cells and the oocytes respectively.
Keywords: Chemistry, Biochemistry.